1997
DOI: 10.1097/00005373-199704000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Resuscitation Decreases Susceptibility to Sepsis after Hemorrhagic Shock

Abstract: HTS resuscitation leads to increased survival after hemorrhage and CLP. Marked improvements were observed in lung and liver injury compared with isotonic resuscitation. The better containment of the infection observed with HTS resuscitation corresponds to a marked decreased in bacteremia. HTS resuscitation stands as an alternative resuscitation regimen with immunomodulatory potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(99 citation statements)
references
References 26 publications
7
82
0
10
Order By: Relevance
“…Our findings are consistent with several previous studies in which intravenous hyperosmolar infusions were reported to prevent lung injury (5)(6)(7)(8). However, for the consideration of hyperosmolar infusion in clinical therapy, the role of the endothelium must be further clarified especially with regard to the manner in which barrier protection is initiated and is maintained in intact models of lung injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with several previous studies in which intravenous hyperosmolar infusions were reported to prevent lung injury (5)(6)(7)(8). However, for the consideration of hyperosmolar infusion in clinical therapy, the role of the endothelium must be further clarified especially with regard to the manner in which barrier protection is initiated and is maintained in intact models of lung injury.…”
Section: Discussionsupporting
confidence: 92%
“…Hyperosmolar infusions, which are commonly applied in resuscitation therapy (4), suppress lung injury (5)(6)(7)(8), inhibit expression of endothelial leukocyte adhesion molecules (8,9), and block the proinflammatory effects of lipopolysaccharide (8). Furthermore, hyperosmolar infusions expand blood volume (10,11) and cause hemodilution (10), suggesting that the capillary barrier remains intact despite the potential cellshrinkage effect of hyperosmolarity (12).…”
Section: Introductionmentioning
confidence: 99%
“…45 More recently, a series of experiments have shown that hypertonic saline solution, even without dextran, significantly interferes with the immune responses, both in vitro and in vivo. [46][47][48][49][50][51][52][53][54][55][56][57] The addition of hypertonic saline solution to a lymphocyte culture media, in concentrations similar to those obtained with systemic infusion of 4 mL/kg of 7.5% NaCl in humans, determined a significant increase in lymphocyte proliferation. 46 The addition of prostaglandin E 2 (PGE 2 ) to the culture media, in the absence of hypertonic saline, caused a reduction in T-cells proliferation, when compared to control cultures.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
“…The rationale for selecting cecal ligation and puncture (CLP) as a septic model is that CLP induces effects analogous to a perforated appendicitis. 3,6,7 The infectious milieu promotes microbial growth or impairs host defenses, which can be quickly modified by surgical source control. 3,5 Therefore, surgical removal of the septic focus has been applied as a key component of success in therapy of ongoing sepsis.…”
Section: Introductionmentioning
confidence: 99%